Correlation of NO and ET-1 Levels with Blood Pressure Changes in Hemodialysis Patients after Arteriovenous Fistula Surgery - Li, Yanli; Lu, Hanxiao; Sun, Yu (Frontiers in Surgery, 2022)
Hemodialysis (HD) is the most common renal replacement therapy for patients with end-stage renal disease (ESRD) and can significantly reduce mortality and improve the quality of life of patients. The occurrence of intradialytic hypotension and intradialytic hypertension are important risk factors for death and disability during dialysis in patients with ESRD, yet their etiology remains unclear, and some studies suggest that nitric oxide (NO) and endothelin-1 (ET-1) may play an important role in these hemodynamic alterations. For this purpose we examined the changes in NO and ET-1 levels during hemodialysis in 30 patients on maintenance hemodialysis (MHD) after arteriovenous fistula surgery. The 30 dialysis patients were divided into three groups according to the changes in blood pressure during hemodialysis: patients with stable blood pressure during dialysis were group I; patients with low blood pressure during dialysis were group II; and patients with high blood pressure during dialysis were group III. Blood pressure of MHD patients were measured Pre-dialysis (Pre-D), at 1 hour of dialysis (1h-D), at 2 hours of dialysis (Mid-D, 2h-D), at 3 hours of dialysis (3h-D), and at the end of dialysis (Post-D); and blood samples were taken from the arterial end at Pre-D, Mid-D, and Post-D to measure NO and ET-1 levels. The results of the analysis showed that as dialysis proceeded and ended, the NO levels in the three groups gradually decreased, with significant differences compared with those before dialysis (P < 0.05); the ET-1 levels in group III gradually increased, with significant differences compared with those before dialysis (P < 0.05), while the increasing trend of ET-1 levels in group I and group II was not significant. The increasing trend of MAP in group I was not significant (P>0.05); the MAP in group II showed a gradually decreasing trend, and the MAP Post-D was significantly lower than that Pre-D (P<0.05); the MAP in group III showed an increasing trend , and the MAP Post-D was significantly higher than that Pre-D (P<0.05). Correlation analysis showed a significant positive correlation between ET-1 levels and MAP in Group III at Mid-D (r=0.847, P=0.002).